Eyeball Movement based Cursor and Keyboard Control for Physically Challenged - T.P. , Rani; A. , Bharathi; K. , Suvathy; A. , Priyanka (International Journal of Psychosocial Rehabilitation, 2020)
An individual human-computer interface system using eye movement is introduced. Traditionally, human-computer interfaces use a mouse or keyboard as an input device. The proposed system presents a hands-free interface between the computer and the user for the physically challenged. The main objective is to control the mouse & keypad using the eyeball. It also verifies the user’s authentication using face recognition. For face recognition, the Viola-Jones algorithm is used. The camera is connected with the system & MATLAB is used for user authentication. After successful authentication, the camera continues to scan the user’s eyeball movement. During this state of action, our physical keypad & mouse are frozen in order to stop the user’s key inputs. On-screen keyboard & mouse control is initiated so as to control those through eyeball movements. MATLAB software plays a vital role in controlling the on-screen keyboard and mouse. We will be using Java for freezing the physical keypad & mouse functionalities. The camera scans the eyeball of the authenticated user, and control of the mouse is achieved through the eyeball movement. Alphabets are selected by eye-ball clicking for effective communication. The physical keyboard control is released by the Control, Alt & Delete keys. MATLAB is used for face recognition & eyeball control. The on-screen keyboard is initiated& freezing of the physical mouse & keypad is achieved by Java software.